2013
DOI: 10.1111/1574-6968.12093
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of haem-binding sites in the actinobacterial protein HbpS

Abstract: The extracellular haem-binding protein from Streptomyces reticuli (HbpS) has been shown to be involved in redox sensing and to bind haem. However, the residues involved in haem coordination are unknown. Structural alignments to distantly related haem-binding proteins from Mycobacterium tuberculosis were used to identify a candidate haem-coordinating residue, and site-directed mutagenesis with UV/Vis spectroscopy was used to assess haem binding in vivo and in vitro. We present strong evidence that HbpS belongs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Such a K d value in heme-sensing proteins might be an indication of a flexible heme-binding pocket that is required during sensing of heme. From structural comparisons (27), one knows that HbpS is similar to the heme binding domains within DosS and DosT from Mycobacterium tuberculosis. These are two-component membrane-bound kinases that are involved in heme sensing (61,62).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such a K d value in heme-sensing proteins might be an indication of a flexible heme-binding pocket that is required during sensing of heme. From structural comparisons (27), one knows that HbpS is similar to the heme binding domains within DosS and DosT from Mycobacterium tuberculosis. These are two-component membrane-bound kinases that are involved in heme sensing (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli strains BL21(DE3)pLysS and DH5␣ were cultivated in LB medium. The plasmid vector pETM11 as well as the plasmid constructs pETHbpS, pETHbpS-H28A, pETHbpS-H51A, pETHbpS-H156A, pETHbpS-T113A, and pETHbpS-T113H (27,28,32) were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein-DNA interaction studies revealed that the phosphorylated response regulator SenR activates the transcription of furS , cpeB , hbpS , senS and senR [32], [33]. HbpS is a novel type of haem-binding protein and is secreted via the twin-arginine translocation (Tat) pathway [34], [35]. High resolution 3D crystal structures (PDB: 3FPV and 3FPW) of HbpS reveal an octameric assembly; analyses of electron density maps followed by mutagenesis and biochemical studies showed that a serine (Ser-26) and a histidine (His-28) within the N-terminal domains from neighboring subunits are crucial for oligomerization as well as for interaction with SenS-SenR [36].…”
Section: Introductionmentioning
confidence: 99%